Validation of Quetiapine Fumarate in Pharmaceutical Dosage by Reverse-Phase HPLC with Internal Standard Method - Kiran B. Venkata; Sreenivas Rao Battula; Somshankar Dubey (Journal of Chemistry)
A rapid, specific, and accurate isocratic HPLC method was developed and validated for the assay of quetiapine fumarate in pharmaceutical dosage forms. The assay involved an isocratic-elution of quetiapine fumarate in Grace C18 column using mobile-phase composition of 0.1% ortho phosphoric acid with triethyl amine as modifier buffer and acetonitrile in the ratio of 50 : 50 (v/v).The wavelength of detection is 294 nm. The method showed good linearity in the range of 2.0–50.2 × 10−3 g/Lt. The runtime of the method is 5 mins. The developed method was applied to directly and easily analyse of the pharmaceutical tablet preparations. The percentage recoveries were near 100% for given methods. The method was completely validated and proven to be rugged. The excipients did not interfere in the analysis. The results showed that this method can be used for rapid determination of quetiapine fumarate in pharmaceutical tablet with precision, accuracy, and specificity.